PENINGKATAN KUALITAS HIDUP MASYARAKAT MELALUI EDUKASI DAN DETEKSI DINI HIPERTENSI - Hoesny, Rezkiyah; Hoesny, Munafrin; Nursam, Nasrullah (Universitas Methodist Indonesia, 2023)
Hypertension is a risk factor for terminal illnesses such as heart failure and stroke, where this disease can interfere with daily activities and make people feel anxious easily, resulting in a decrease in quality of life. Health education and early detection through blood pressure checks are promotive and preventive efforts in treating hypertension. The implementation of community service carried out in the To'bulung sub-district, Palopo City, was successfully carried out. Blood pressure checks can identify the risk of hypertension and providing education can provide information about the etiology, clinical manifestations, complications, treatment and prevention of hypertension. Providing education through lecture methods, discussions and providing leaflets is effective in increasing public knowledge about hypertension in the To'bulung sub-district. This method can stimulate public curiosity about hypertension, especially its treatment and prevention. Routine blood pressure checks and providing education can increase people's knowledge and change their behavior to lead a healthy lifestyle. Maintaining physical condition will provide a sense of comfort and thus have an impact on the quality of life of hypertension sufferers.